Does accounting for taxes on income provide information about tax planning performance? Evidence from German multinationals - Michael Overesch; Ulrich Schreiber (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper investigates the quality of information on tax planning performance which is provided by financial accounting based on IAS 12 (Income taxes). A simple theoretical investment model is used to show that reported tax expenses can be misleading as an indicator of tax planning performance, since timing effects of tax depreciations are suppressed. However, it is shown that IAS 12 provides meaningful information if tax planning strategies are driven by statutory tax rate differences, e.g. in the case of profit shifting. Our empirical analysis of actual tax planning behaviour, based on a panel of German balance sheet data, suggests that in practice international tax planning is significantly driven by statutory tax rates. However, we find that tax depreciation impacts on the size of investment as well and thus, IAS 12 does not fully disclose tax planning performance.
Keywords: 330; International Taxation; Financial Accounting; Income Taxes; Firm-level Data